Labor Boundaries and Skills: The Case of Lobbyists - Espinosa, Miguel (Management Science, 2021)
What are the determinants of in-house employment versus outsourcing in the service sector? I use detailed data on U.S. lobbying services to answer this question. I argue with a series of correlational exercises that firms tend to outsource lobbying tasks that demand a large amount of general skills, whereas they are more likely to assign firm-specific tasks to in-house lobbyists. I provide causal evidence that the need to do tasks that vary in their general skill component leads to a change in outsourcing. Using difference-in-difference estimations, I show that the 2010 British Petroleum oil spill increased the general skills needed by oil and gas firms and that, consequently, their use of lobbyists for hire increased. This paper was accepted by Joshua Gans, business strategy.